CURRICULUM AND PEDAGOGICAL DEVELOPMENT IN ELEMENTARY EDUCATION IN INDIA UNDER NEP 2020 - Tungoe, Chumdemo (International Journal of Research -GRANTHAALAYAH, 2024)
The National Educational Policy (2020). is a policy formulated by the Government of India to reform the education system in India. It replaces the NEP 1986 in order to meet the educational requirements of the 21st Century. The NEP 2020 aims to make “India a global knowledge superpower”. It is the third major framework in the constitutional framework in the field of education. Unlike its former predecessor the National Educational Policy (2020) completely revamps the educational policy of 1986 and lays down a new foundational system of education among primary students by emphasising life skills along with education. The policy focuses on other aspects like multidisciplinary and holistic education, conceptual understanding, creative & critical thinking, multilingualism, and several other aspects of cognitive development.